Doping in sport: New developments - Krych, K.; Gozdzicka-Jozefiak, A. (Human Movement, 2008)
Gene doping is defined by the World Anti-Doping Agency (WADA) as "the non-therapeutic use of genes, genetic elements and/or cells that have the capacity to enhance athletic performance." The rapid development of molecular biology has enabled not only treatment of many diseases, but also improvement of athletes' fitness. Gene therapy methods can be used to modify the athlete's body by inserting genes into the target tissue. It is very possible that in near future, many genes will be used in gene doping, e.g. erythropoietin, growth hormone, insulin-like growth hormone and vascular endothelial growth factor. Functional tests conducted by many independent laboratories proved that products of these genes exert a crucial influence on the body's adaptation to exercise. The risk of gene doping is enormous. Gene therapy is currently in the phase of clinical tests so it is impossible to predict what kind of side effects it may produce. Studies on animal models showed that the uncontrolled transgene expression and insertional mutagenesis can even lead to death. At present the detection of gene doping is very difficult for a variety of reasons. The main problem is the identification of the transgene and endogenously produced protein. The only possible detection is the biopsy of the target tissue, where the exogenous genes were inserted.